Organisational support for high-performance athletes to develop financial literacy and self-management skills - Hee Jung Hong; Ian Fraser (Journal of Risk and Financial Management, 2022)
This paper reports the results of analysing desk-based data on organisational support for high performance athletes to develop their financial literacy and self-management skills when transitioning out of sport. There are two research questions: (1) Do sport organisations provide support schemes or other interventions such that high-performance athletes develop their financial literacy and self-management skills? and (2) Do sport organisations provide financial support schemes for high-performance athletes' retirements? If so, what do they involve? Desk-based data collection was applied to 23 sporting organisations; these comprised 21 national organisations representing 19 countries, the International Olympic Committee (IOC) and the Oceanic National Olympic Committee (ONOC). Fifteen of the 23 organisations, representing 14 countries, provided some support or interventions on financial planning and self-management within their career assistance programmes. The findings also indicate that most organisations in 17 different countries did not provide any financial support for athletes' retirements. While a number of sport organisations have developed appropriate interventions to assist high-performance athletes to develop financial literacy and self-management skills, such schemes appear only to be provided to high-performance athletes who have competed at the highest level e.g., Olympics, world championships, etc. Support for athletes at lower levels should also be developed and delivered by national governments, or by national sport organisations.
Keywords: 330; financial literacy; financial well-being; organisational support; career transitions in sport; career development and self-management